AKTIVITAS SITOTOKSIK ISOLAT 5 FRAKSI ETIL ASETAT EKSTRAK PETROLEUM ETER DAUN Phaleria macrocarpa (Scheff.) Boerl. PADA TURUNAN SEL KANKER SERVIKS MANUSIA (HeLa) - Dwi Utami (Pharmaciana, 2011)
Cervical cancer is a malignant tumor in cervix which is occupy the second possition that cause the death of Indonesia’s women under the breast cancer. One of the traditional medicine that can be used to cure cancer is Phaleria macrocarpa (Scheff.)Boerl leaves. The petroleum eter extract of Phaleria macrocarpa (Scheff.)Boerl leaves has antiproliferation activity againts cervical cancer cell lines (HeLa) with IC50 9 µg/ml (Kintoko & Azimahtol Hawariah, 2007). This research was aimed to detect cytotoxic activity of isolate 5 of ethyl acetate fraction of petroleum ether extract of Phaleria macrocarpa (Scheff.)Boerl leaves againts HeLa cell lines. Initially, the powder of Phaleria macrocarpa (Scheff.)Boerl was extracted using Soxhlet apparatus with petroleum ether. The extracts was concentrated and partitioned until ethyl acetate fraction was obtained. The fraction of ethyl acetate was isolated using Preparative Thin Layer Chromatography on silica gel F254 as stationary phase and n-hexane : ethyl acetate (9 : 1) as mobile phase. Cytotoxic activity against HeLa cell lines was determinated by LC50 value by direct counting. The isolation by preparative thin layer chromatography resulted five isolate on Rf value : 0,05 ; 0,10 ; 0,20 ; 0,60 ; and 0,90. The LC50 values of isolate 5 (Rf : 0,90) was 123,60 µg/ml.